2019
DOI: 10.1002/adsc.201900906
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Selective N‐Methylation and N‐Formylation of Amines with CO2

Abstract: We herein describe an efficient iron‐catalyzed selective N‐methylation and N‐formylation of amines with CO2 and silane using mono‐phosphine as ligand. With commercially available [CpFe(CO)2]2 as catalyst, Fe‐catalyzed methylation of amines was achieved with triphenylphosphine as a ligand. Using tributylphosphine as a ligand, Fe‐catalyzed formylation of amines was realized at a lower temperature. The method was successfully applied in the late‐stage methylation and formylation of drug molecules containing amine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 83 publications
0
32
0
2
Order By: Relevance
“…10,11 Thus, use of CO 2 as a methylating reagent under a reductive atmosphere is an attractive alternate to produce N-methyl amines through direct functionalization of amines. In the last decade, several metal catalysts [12][13][14][15][16][17][18][19][20][21] and a few metal-free catalysts [22][23][24][25] were reported for this catalytic transformation in presence of hydrosilanes as a reducing agent and all of these studies were carried out at an elevated temperature. However, these methods have very limited potential towards consecutive N-methylation involving primary amines.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Thus, use of CO 2 as a methylating reagent under a reductive atmosphere is an attractive alternate to produce N-methyl amines through direct functionalization of amines. In the last decade, several metal catalysts [12][13][14][15][16][17][18][19][20][21] and a few metal-free catalysts [22][23][24][25] were reported for this catalytic transformation in presence of hydrosilanes as a reducing agent and all of these studies were carried out at an elevated temperature. However, these methods have very limited potential towards consecutive N-methylation involving primary amines.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the most abundant metal in the earth and inexpensive Fe complexes could also serve as an efficient catalyst. The research group of Xia demonstrated homogeneous [CpFe(CO) 2 ] 2 catalyst in combination with triphenylphosphine or tributylphosphine as ligands for N ‐methylation and N ‐formylation of amines in the presence of CO 2 and PhSiH 3 [26] . The reaction conditions were optimized using N ‐ethylaniline as a model substrate (Table 4).…”
Section: N‐methylation Reactions Using Co2 As a Carbon Sourcementioning
confidence: 99%
“…It is also noteworthy that the authors further extended the scope of the method to the late‐stage N ‐methylation of biologically active pharmaceuticals (atomoxetine, sertraline, cinacalcet, and paroxetine) and obtained the respective N ‐methylated products in moderate to good yields (30‐78%) (Scheme 7). [26] …”
Section: N‐methylation Reactions Using Co2 As a Carbon Sourcementioning
confidence: 99%
“…The present method is assumed to be potentially useful for the application to late-stage functionalization of bioactive molecules containing aromatic N-methyl group. 18…”
Section: Scheme 3 Site-selectivity Of C(sp 3 )-H Amidation Of N-alkylmentioning
confidence: 99%
“…It is worthy to note that benzylic methyl C(sp 3 )-H bonds of toluene were totally inactive for amidation, even when toluene was used as a solvent (entry 15). Use of bases such as Li2CO3, Na2CO3, Cs2CO3, or Rb2CO3 did not improve the yield of the amidation reaction (entry 15 vs [16][17][18][19][20]. Finally, the yield of amidation was improved by use of 10 equivalents of the substrate to afford the desired 2aa in 79% yield (entry 21).…”
mentioning
confidence: 99%